2020
DOI: 10.1111/tid.13260
|View full text |Cite
|
Sign up to set email alerts
|

The QuantiFERON Monitor® assay is predictive of infection post allogeneic hematopoietic cell transplantation

Abstract: Introduction Following allogeneic hematopoietic stem cell transplantation (alloHCT), excessive immunosuppression can be complicated by infection, while inadequate immunosuppression can result in graft‐vs‐host disease (GVHD). An accurate method to assess overall immune status post HCT is lacking. The QuantiFERON Monitor® (QFM) assay measures interferon gamma (IFN‐γ) release from whole blood following incubation with both innate (Toll‐like receptor 7, TLR7) and adaptive (CD3 antibody) stimulants and may result i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…There is increasing interest in WB-based profiling of adaptive immune responses in infectious diseases and, to that end, a number of investigational and commercial assay systems have been developed [17,46]. WB assays for the detection of antigen-reactive T-cells have several important advantages over their PBMC-based counterparts as they require less blood volume and hands-on-time, facilitate improved standardization, and are often more cost-efficient [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing interest in WB-based profiling of adaptive immune responses in infectious diseases and, to that end, a number of investigational and commercial assay systems have been developed [17,46]. WB assays for the detection of antigen-reactive T-cells have several important advantages over their PBMC-based counterparts as they require less blood volume and hands-on-time, facilitate improved standardization, and are often more cost-efficient [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these drawbacks, there is a growing interest in the development of whole blood (WB)-based protocols to determine T-cell responses to fungal antigens [15,16], following the clinical success of WB-based tests in tuberculosis and cytomegalovirus (CMV) diagnostics and research [17][18][19]. Although WB assays are more robust than PBMCbased protocols [16], concerns about impaired test performance remain when stimulation conditions are suboptimal, e.g., in the presence of immunosuppressive therapy or after long pre-analytic delays [16,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In fact the QFM levels seen in our cohort were more similar to bone marrow transplant recipients. 12 The ImmuKnow® assay (Cylex/Viracor-Eurofins, USA) is a widely studied immune biomarker that measures adenosine triphosphate (ATP) release from CD4+ T-lymphocytes after phytohemagglutinin-L (PHA) stimulation, which is thought to represent T-cell function. 4,21,22 Despite being FDA approved in 2002, there has not been widespread clinical uptake in this test mainly due to difficulties in defining cutoffs…”
Section: Discussionmentioning
confidence: 99%
“…11 More recently, QFM has been evaluated in bone marrow transplant recipients and low levels were associated with infections during the pre-engraftment period. 12 An improved ability to measure net state of immunosuppression would allow for individualization of immunosuppressive therapy before clinical events occur, potentially minimizing the risk of both under-immunosuppression leading to rejection and over-immunosuppression resulting in infection and drug toxicity. The aims of this study were to evaluate QFM both as a biomarker of immunosuppression and as a tool for the prediction of infection and rejection in a prospective observational cohort of lung transplant recipients (LTR).…”
Section: Back Groundmentioning
confidence: 99%
“…8,35 Recent studies reported that the ELISPOT assay for IFN-γ secretion of HCMV-specific CD8 + T cells performed well at predicting recurrent HCMV reactivation. 6,36 The HCMV serostatus of the patient and donor is one of the most important variables influencing HCMV-specific T cell immune reconstitution. 37,38 HCMV-seropositive recipients and donors (R + D + ) have a much faster reconstitution of HCMV-specific CD8 + T cells than HCMV-seropositive recipients transplanted from HCMVseronegative donors (R + D − ).…”
Section: Relationship Between Hcmv-igg Antibody and Ifn-γ Sfcs Countsmentioning
confidence: 99%